Correspondence respecting the Behring Sea seal fisheries, 1886-90 [electronic resource]. - Great Britain. Foreign Office. (London : Printed for H.M.S.O. by Harrison, 1890)
Original issued in series: [Command papers / Great Britain. Parliament] Cd. 6131. Attributed to Great Britain. Foreign Office--A bibliography of British Columbia / Barbara J. Lowther. At head of title: United States. No. 2 (1890). "Presented to both Houses of Parliament by Command of Her Majesty. August 1890." Electronic reproduction. Mode of access: Internet. 44